Legal Aspects of Online Business and COVID-19: Data Insights - Sarigati, Pandu; Mediawati, Noor Fatimah; Indakto, Ratro (Proceedings of The ICECRS, 2023)
This data article presents findings from a Lens.org search targeting scholarly articles at the nexus of online business and COVID-19, specifically within the realm of law. Initiated with a keyword search, 9,016 documents were initially identified, refined to 7,204 by filtering for "journal article" and "conference proceeding." Subsequent application of the "law" filter yielded 83 pertinent scientific articles. The amassed data serves as a foundation for future research endeavors and offers a valuable reference for scholarly journals delving into the legal implications of the COVID-19 pandemic on online business operations. Highlights: Initial search yielded 9,016 documents, refined to 83 pertinent scientific articles at the intersection of COVID-19, online business, and law. Filtering criteria included "journal article" and "conference proceeding," streamlining the focus for relevance and scholarly rigor. Significance lies in providing a comprehensive foundation for future research and acting as a vital reference for scholarly exploration of the legal aspects surrounding COVID-19's impact on online business. Keywords: Online Business, COVID-19, Legal Implications, Scholarly Articles, Law